Pré-condicionamento com l-alanil glutamina sobre o estresse oxidativo e inflamação em enxertos de pacientes submetidos ao transplante de fígado - Barros, Marcos Aurélio Pessoa (2014)
In liver transplantation, ischemia/reperfusion may cause serious injury to the graft. The aim of this study was to evaluate the effects of preconditioning with L-alanyl-glutamine in graft protection in patients undergoing liver transplantation. 33 patients undergoing liver transplantation at the Walter Cantídio University Hospital (HUWC) of the Federal University of Ceará (UFC), from 05/22/13 to 12/11/2013 were evaluated. A prospective, double-blind, divided into two groups was performed. In glutamine group was administered 50 g of L-alanyl glutamine, 40 minutes before the start of cold ischemia, the control group, saline solution was administered. Donor age, degree of graft steatosis, warm ischemia time (WIT), cold ischemia time (CIT), MELD score, graft survival, and receptor mortality were evaluated. Graft biopsies were performed at the beginning of donor surgery at the beginning of warm ischemia and at the end of transplantation. With these samples, MDA (malondialdehyde), HSP70, NFkB, SOD and glutathione were measured. In multiple organ donor, were measured AST, ALT, bilirubin and INR. The same parametheas in the receiver, were measured on admission in the hospital at the beginning of warm ischemia, at the end of transplantation in the 1st postoperative day (POD), in the 3 rd, the 5th, on the 7th and 30th POD. There was no difference between the two groups with respect to donor age, receiver age, CIT, WIT, MELD and degree of steatosis. The results of serum tests were similar in both groups. In the Glutamine group, MDA in the grafting did not increase at the beginning of warm ischemia and impairment occurred at the end of transplantation. This phenomenon did not occur in the control group. Glutathione, SOD, HSP70, NFkB were similar in both groups. This study suggests that preconditioning with glutamine minimizes the effects of oxidative stress caused by ischemia and reperfusion, with decreased lipid peroxidation in the graft of patients undergoing liver transplantation.